Maternalism and Latin American Feminist Discourses on Caregiving Work: A Fabric in Tension - Roberta Liliana Flores; Olivia Tena Guerrero (Íconos)
With the objective of identifying the specificity of the Latin American feminist discussion on the work of caregiving, several overlapping elements are analyzed that define it. The centrality of the maternal figure and the family ideology that emphasizes the relational character of caregiving is highlighted and the consequent tensions in feminist debates before the definition of care as work are analyzed. From a critical perspective of the “caregiving ethic,” the construction of a conceptual framework is discussed, one that is composed of the concept of the sustainability of life and the notion of caregiving as a human right, which reconciles the responsibility and the obligation of caregiving work in its material and relational characters in its construction as a public problem in the region.